A Test of the General Validity of the Heckscher-Ohlin Theorem for Trade in the European Community - Hakura, Dalia (Washington, D.C. : International Monetary Fund, 1999)
While the Heckscher-Ohlin-Vanek (HOV) theorem has been a dominant paradigm in trade theory, the empirical evidence to support it has been weak. This paper develops a modified HOV model that allows technologies to differ across countries. The revised model significantly improves the theory's accuracy in predicting trade flows in contrast to the traditional model. The paper also illustrates that, since countries have different technologies, measures of factor contents of trade in final goods using direct and domestically produced indirect input requirements are more accurate and yield more consistent predictions than do traditional measures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet